On the association between risk attitude and fruit and vegetable consumption: Insights from university students in Italy - Elisa Giampietri; Giuseppe Bugin; Samuele Trestini (Agricultural and Food Economics, 2021)
As a novel contribution, this paper explores the possible association between individual risk attitudes and consumer fruit and vegetable (FV) intake. Inspired by the literature, the study also investigates the relationship between FV consumption frequency and health consciousness, perceived health benefits, trust, and attitude towards eating the recommended five-a-day FV portions. An ordered logit model is estimated on data collected through direct interviews among university students. The results show that risk aversion has a positive effect on consumer choice to eat the recommended number of FV servings, similar to the individual health consciousness and the perception of health benefits. The results pave the way for new research that aims to provide useful evidence for the implementation of new strategies to foster people's FV intake in compliance with the five-a-day recommendation.
Keywords: 330; Consumer behaviour; Fruit and vegetable intake; Health benefit; Healthy diet; Risk attitude